Tratamiento penitenciario de resocialización y reincidencia en interno(as) del Penal de Varones y Mujeres, Iquitos 2020 - Meza Carrizales, Anibal Rafael (2022)
The purpose of the research study was to know the effectiveness of the treatment program in the resocialization of repeat offenders. The question posed was: What is the relationship between resocialization prison treatment and recidivism in inmates of the Men's and Women's Prison of the city of Iquitos, 2020? The general objective: To determine the relationship between resocialization prison treatment and recidivism in inmates of the Men's and Women's Prison of the city of Iquitos, 2020. The study method was quantitative, type of descriptive study, and non-experimental, cross-sectional and correlational design; the sample consisted of 193 repeat offenders. The instrument used was a Likert scale, with validity 84.5% and reliability 83.7%. The results were: of the 100% (193) inmates who are repeat offenders, 65.8% (127) report that the prison treatment program of the services (Global) it provides for the resocialization of inmates is deficient and 34.2% (66) report that it is efficient. 51.8% (100) have recidivism due to lack of job opportunity and absence of inclusion laws or lack of a family home (multicausal), 48.2% (93) present recidivism for a single cause of those described above (unicausal). Concluding that there is a statistically significant relationship between the treatment of resocialization and recidivism in inmates of the male and female prison of the city of Iquitos, 2020 where a value of X2c=9.589 p=0.002 GL=1 ?=0.05 was obtained, which is < to ? = 0.05. The results contribute to strengthening the treatment program, redesigning crime prevention strategies that allow effective attention to resocialization of the prison community, and thus prevent recidivism and stop the cycle of failed social integration.